Influence of Water Inrush from Excavation Surface on the Stress and Deformation of Tunnel-Forming Structure at the Launching-Arrival Stage of Subway Shield - Shusheng Lv; Wen Liu; Shihong Zhai; Peishuai Chen (Advances in Civil Engineering)
The launching-arrival stage of the shield is the most dangerous construction stage in subway construction. During the conversion process of the soil and air medium in the shield machine, water inrush at the excavation surface often occurs because of the effect of groundwater. Previous research has focused on the overall stress and deformation of existing tunnels caused by water inrush from the excavation face of the shield machine excavation stage. However, the stress and deformation states of the segments and anchors at different assembly locations of the tunnel, as well as the interaction between the soil reinforcement region and the segments and anchors in the launching-arrival stage have not been considered in previous studies. In this study, the inrush model of the launching-arrival stage of the subway shield was established by utilizing the equivalent refinement modeling technology and ABAQUS simulation analysis with consideration of the fluid-solid coupling effect of water and soil to study the influences of different water head differences on the mechanical and deformation properties of segments and anchors in shield construction under the conditions of water inrush on the excavation surface. The results showed that the water inflow from the tunnel excavation surface caused significant surface subsidence at the tunnel portal, vertical convergence at the cross section of the shield tunnel, and significant increases in the axial and shear forces on the bolt. In addition, based on the existing subway regulation, combined with the simulation results of soil reinforcement measures at different depths, the emergency control criterion for controlling water inrush on the excavation surface was established by using the depth of soil reinforcement. The minimum depth of the reinforced soil from the ground surface at 15 m is recommended to ensure construction safety of the subway shield at the launching-arrival stage.